FINANCIAL ACCOUNTABILITY IN UDI AND EZEAGU LOCAL GOVERNMENT BUREAUCRACIES - Ugwueze Charles Afamuefuna (Innovative Issues and Approaches in Social Sciences)
The specific objectives of this research were to: ascertain if internal financial control measures are properly adhered to in the two local governments; determine if external auditing is playing its strategic role effectively in the financial control of the two local governments; ascertain whether there are adequate authorization and recordings to provide reasonable accounting controls over revenue and expenditure in the two local governments; and ascertain the relationship between the local government legislature and executive in ensuring financial control in the two local governments. Descriptive survey research was adopted in interrogating the aforementioned objectives. The population of the study is 1200 employees from Finance, works, education, administration, health and agriculture departments of the two local governments under study. In order to get a representation of the whole population the Taro Yamani formular for sample size determination was used. It found that internal control measures are not properly adhered to in the two local governments; external auditing is not effectively playing its strategic role in the financial control of the two local governments; Udi and Ezeagu local governments do not maintain authorization and recordings to provide reasonable accounting controls over revenue and expenditure; and there is no effective system of checks and balances between the local government legislature and executive for financial control in the two local governments. The results imply that the local government functionaries in Udi and Ezeagu local government do not adhere to the principles of financial accountability in the conduct of the affairs of the council.